Produção de tanase por Cunninghamella echinulata UCP 1305 através de fermentação submersa utilizando meios alternativos contendo resíduos agroindustriais. - Paiva, José Bezerra de Paiva (2019)
Microbial enzymes have increased their production in the last decades, due to their enormous versatility in several industrial processes. Tannin acyl hydrolase (EC 3.1.1.20) or tannase is an enzyme that exhibits great versatility and is directly involved in the hydrolysis of esters and side-links of tannins. This enzyme is produced mainly by several genera of filamentous fungi, yeasts and bacteria. Studies involving samples of Cunninghamella echinulata (UCP 1305 and 1308), isolated from Caatinga soil samples from the city of Serra Talhada in the State of Pernambuco, Brazil, where different temperatures (28 and 37 ºC) and pH (4.5, 5.5) were initially tested , 6.5, 7.0 and 8.0) in solid medium for 120 hours, with daily monitoring. After the selection of the best production sample, enzymatic production studies were carried out using submerged fermentation using four different chemical composition media for 120 hours, 37 oC and 150 rpm. In these tests, the microbial growth curve, pH variation and the enzymatic determination of the samples were evaluated every 24 hours. After the selection of the best production medium, tests were carried out involving factorial planning of 22 with media containing agroindustrial residues (grape residue , peels of oranges and coffee) under the same conditions of the previous control medium. The results showed that the sample Cunninghamella echinulata UCP 1305 demonstrated the production of tannase in solid medium through the appearance of the halo characteristic of the enzyme tested (4,5 cm), with values of pH of 7.0 and temperature of 37 oC. In the submerged fermentation experiments, the best results of the enzymatic activity were obtained in the medium named 3, pH of 6.58 and activity of 0.413 U / mL, being denominated control medium. The assays using alternative media containing agroindustrial residues, showed that the medium containing grape residue at 3% presented maximum tanase activity (0.371 U / mL) when compared to the other media tested under the same conditions. It is verified that the use of means using agroindustrial residues rich in tannins appears as a promising alternative in the fermentative processes, because they reduce the environmental pollution and generate biotechnological products of high added value for the industries.